Numerical Rule-Learning in Ring-Tailed Lemurs (Lemur Catta) - Merritt, Dustin; MacLean, Evan; Crawford, Jeremy C.; Brannon, Elizabeth M. (Frontiers in Psychology, 2011)
We investigated numerical discrimination and numerical rule-learning in ring-tailed lemurs (Lemur catta). Two ring-tailed lemurs were trained to respond to two visual arrays, each of which contained between one and four elements, in numerically ascending order. In Experiment 1, lemurs were trained with 36 exemplars of each of the numerosities 1-4 and then showed positive transfer to trial-unique novel exemplars of the values 1-4. In Experiments 2A and 2B, lemurs were tested on their ability to transfer an ascending numerical rule from the values 1-4 to novel values 5-9. Both lemurs successfully ordered the novel values with above chance accuracy. Accuracy was modulated by the ratio between the two numerical values suggesting that lemurs accessed the approximate number system when performing the task.